Implementasi Employer Branding untuk Menarik Talenta Berkualitas dalam Recruitmen Marketing - Syafiq Nur Iman; Tiara Hikmah J; Desi Ratnasari; Gilang Maulana S; Andira Triantika N; Roica Sholikhatun; Yoki Nawan Gunara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Competition in recruiting high-quality talent has intensified due to the advancement of digital technology, globalization, and the shifting preferences of younger generations in choosing their workplace. Traditional recruitment models are no longer sufficient, requiring companies to integrate employer branding with recruitment marketing strategies to attract potential candidates effectively. This study aims to analyze how PT Surya Pratista Hutama (SUPRAMA), a food manufacturing company, implements employer branding to strengthen its corporate image and enhance recruitment effectiveness. The research employed a qualitative descriptive method through observation, interviews, and documentation studies with the Human Capital and Corporate Communication Division. The findings reveal that SUPRAMA’s employer branding strategy is carried out through organizational culture strengthening, the use of digital platforms, consistent visual identity, and collaboration with educational institutions. The integration of these strategies has proven to increase the number of qualified applicants, improve candidate experience, and enhance the company’s reputation as an employer of choice. However, challenges remain in maintaining consistent branding communication and developing innovative digital content. This study concludes that employer branding is not merely a communication tool but also a long-term investment in human resource management.